Spare Any Change ? : Power and Discourse in Toronto’s Urban Panhandling Subculture - Warner, Karen; Butler, Gary (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1996)
This article is the resuit of fieldwork carried out alongside panhandlers on the streets of Toronto, whose discourse is gleaned for dues to cultural norms and ideas about social belonging. The life stories of panhandlers are summarized in order to set the scene and their modus operandi is described in some detail. Particular attention is paid to the ways in which panhandlers “other” certain segments of society (including fellow panhandlers who refuse to abide by the common code of behaviour), often reflecting the mainstream ideology they profess to reject. One of the authors spent several stretches actually panhandling amid their informants, in order to better understand this seemingly permanent feature of urban living today.